2018
DOI: 10.1002/cmdc.201700792
|View full text |Cite
|
Sign up to set email alerts
|

Structure–Activity Relationship Studies of Vitamin D3 Analogues Containing an Ether or Thioether Linker as Hedgehog Pathway Inhibitors

Abstract: The Hedgehog (Hh) signaling pathway is critical for embryonic patterning and postembryonic tissue regeneration. Constitutive pathway activation has also been linked to human malignancies such as basal cell carcinoma (BCC) and medulloblastoma; therefore, multiple small-molecule scaffolds that inhibit Hh signaling are in development. Previously, Grundmann's alcohol, also known as the "northern region" of vitamin D3 (VD3), has been identified as a moderate Hh pathway inhibitor. In this study, isomers of Grundmann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…To continue our SAR exploration of this region of the scaffold, we sought to synthesize and evaluate analogues that continue the scaffold truncation that we previously probed by removing the phenyl ring on the “right side” of the scaffold and directly appending the 3-phenolic carboxylic acid of 2 to the piperazine amine to provide analogue 3 . We evaluated this analogue for its ability to decrease Gli1 mRNA expression in the Hh-dependent murine BCC cell line ASZ001. Analogue 3 demonstrated comparable anti-Hh activity compared to 2 (IC 50 values = 0.26 μM and 0.16 μM, respectively), verifying that this series of compounds retains potent Hh inhibition and encouraging us to synthesize additional analogues that incorporate the 4-phenylpiperazinyl amide.…”
mentioning
confidence: 89%
“…To continue our SAR exploration of this region of the scaffold, we sought to synthesize and evaluate analogues that continue the scaffold truncation that we previously probed by removing the phenyl ring on the “right side” of the scaffold and directly appending the 3-phenolic carboxylic acid of 2 to the piperazine amine to provide analogue 3 . We evaluated this analogue for its ability to decrease Gli1 mRNA expression in the Hh-dependent murine BCC cell line ASZ001. Analogue 3 demonstrated comparable anti-Hh activity compared to 2 (IC 50 values = 0.26 μM and 0.16 μM, respectively), verifying that this series of compounds retains potent Hh inhibition and encouraging us to synthesize additional analogues that incorporate the 4-phenylpiperazinyl amide.…”
mentioning
confidence: 89%
“…To gain in-depth understanding of GA’s alcohol and its analogues as Hh inhibitors, Wen et al 106 recently reported the synthesis and Hh inhibitory potential of GA linked to a substituted phenyl or benzyl ring via an ether or thioether linker. For phenyl-substituted GA isomers and corresponding ether-linked 4-aniline analogues demonstrated potent anti-Hh activity in C3H10T1/2 cells, whereas precursor 4-nitro derivatives were inactive.…”
Section: Recent Advances In Design Of Hh Pathway Inhibitorsmentioning
confidence: 99%
“…The organic synthesis of analogs of vitamins is an active field of interest for medicinal chemistry, pharmaceuticals, and the food additive industry . For instance, vitamin D 3 analogs synthesis has been promoted given its capacity to modulate signaling pathways with the objective of discover desirable effects in cancer cells. We can consider other examples, such as vitamin K analogs, used as possible cancer therapies because of the inhibition produced in the growth of cancer cells by mechanisms, such as apoptosis, cell cycle arrest, and autophagy . In addition, their characteristics may be used to develop stem-cell-based therapies for neurodegenerative diseases .…”
Section: Introductionmentioning
confidence: 99%